Art therapy for emotional regulation in primary school children: an effective approach - Yusoff, Mohd Imran; Ahmad, Nor Shafrin (Journal of Islamic, Social, Economics and Development, 2025)
This paper presents a comprehensive study on the effectiveness of art therapy interventions in enhancing emotional regulation among primary school children, using the PRISMA framework to systematically review 26 relevant studies. Recognizing the crucial role of emotional regulation in a child's development, the research focuses on art therapy as a unique, non-verbal medium for young learners. Art therapy shows substantial power to help children express emotions and manage feelings according to research that follows PRISMA methodology. The study reveals that art therapy offers substantial advantages for educational environments as well as therapeutic settings when promoting complete emotional and psychological growth in primary school children. The study contributes to academic knowledge about child development and validates the educational value of implementing art therapy to provide balanced developmental experiences.